All-polymer active layer and preparation method and application thereof

By designing the all-polymer active layer, using a quasi-plane heterojunction structure and layer-by-layer spin coating process, the problems of short life and poor efficiency stability of organic solar cells are solved, and efficient photoelectric conversion and good cycle stability are achieved.

CN119451375APending Publication Date: 2025-02-14BEIHANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411522755.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing organic solar cells have a short life under photothermal conditions, which is difficult to meet the needs of commercial applications. Moreover, the phase separation scale is large when the polymer donor is blended with the acceptor, resulting in excessive carrier recombination, affecting efficiency. stability.

Method used

Design a fully polymer active layer, adopting a quasi-planar heterojunction structure, the first active layer consists of a polymer donor, and the second active layer consists of a polymer acceptor doped with a small amount of polymer donor, by The layer spin coating process is prepared to optimize the morphology of the active layer, reduce the aggregation between polymer acceptors, and improve the carrier transmission ability.

Benefits of technology

Effectively inhibits the transitional miscibility between polymer donor and acceptor, reduces the recombination of carriers during transmission, improves the photoelectric conversion efficiency of organic solar cells, and significantly improves under high and low temperature conditions. Cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451375A_ABST
    Figure CN119451375A_ABST
Patent Text Reader

Abstract

The invention relates to an all-polymer active layer and a preparation method and application thereof, the all-polymer active layer is of a quasi-planar heterojunction structure, the all-polymer active layer comprises a first active layer and a second active layer arranged on the first active layer, the first active layer comprises a first polymer donor, and the second active layer comprises a second polymer donor. And the second active layer comprises a polymer acceptor and a second polymer donor doped in the polymer acceptor. The invention provides the all-polymer active layer with the quasi-plane heterojunction structure, so that the transition miscibility phenomenon between a polymer donor and a polymer acceptor can be inhibited, and the recombination of carriers in the transmission process is reduced; meanwhile, a small amount of polymer donors are doped in the polymer acceptors in the second active layer, the morphology of the active layer is optimized, aggregation between the polymer acceptors is reduced, and transmission of carriers is promoted, so that the organic solar cell which is excellent in photoelectric conversion efficiency and good in cycling stability under the conditions of high temperature and low temperature is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a full polymer active layer and a preparation method and application thereof. Background Art

[0002] As the economy continues to grow, environmental issues have become increasingly prominent. Therefore, the development of green new energy has become the focus of attention from all walks of life. Among many new energy sources, solar energy is generally considered to be one of the better energy sources. It is worth mentioning that in recent years, my country has actively promoted the development of new quality productivity and continued to increase its support for the photovoltaic field. The vigorous development of photovoltaic technology has brought unlimited possibilities for our future.

[0003] At present, more than 95% of commercial photovoltaic cells use crystalline silicon photovoltaic products. However, this type of battery has some disadvantages, such as high raw material consumption and energy consumption in the purification process, as well as serious environmental pollution. In contrast, organic solar cells have many advantages such as low cost, light weight, semi-transparency, flexible and foldable, and large-scale manufacturing. These advantages make organic solar cells show important application potential in the fields of wearable devices, photovoltaic building integration, etc. With the continuous deepening of research, the efficiency of organic solar cells is currently close to 20%.

[0004] The increasing energy conversion efficiency makes organic solar cells promising for commercial applications. However, to ensure commercial viability, organic solar cells must maintain stable performance during their cycle, which is the key to whether this solar cell technology with great potential can be widely used. Due to the limitations of processing technology and material properties, organic solar cells usually have a short lifespan under photothermal conditions and cannot meet the needs of commercial applications. To solve this problem, designing new interface layer and active layer materials is a direct and effective method. However, the design of new materials often requires a lot of time and effort, and it is difficult to achieve breakthroughs in the short term.

[0005] CN114891026A discloses that a polymer donor material (PBDB-T) is blended with a pyran ring-based AD-π-A type small molecule acceptor material as an active layer, and is applied to a solution-processed polymer solar cell. CN116133443A discloses that a star-shaped non-fullerene small molecule acceptor material and a narrow bandgap polymer donor material can form a good absorption complementarity and energy level matching, thereby improving the open circuit voltage and short circuit current of the device. However, when the polymer donor is blended with the small molecule acceptor, the phase separation scale is large, and there are many donor-acceptor interfaces, which will cause a large number of carriers to recombine at the donor-acceptor interface, which is not conducive to achieving a higher efficiency of the device, and the acceptor stability of the small molecule is poor, which is not conducive to the stable circulation of the battery under high and low temperature conditions.

[0006] CN107359243A discloses a ternary blended organic polymer solar cell device, which greatly broadens the spectral absorption range of the active layer, enabling the device to capture sunlight of a longer wavelength, thereby greatly improving the photoelectric conversion efficiency of the solar cell, and adjusting the ratio between the two electron acceptors can effectively regulate the open circuit voltage and fill factor of the device, thereby improving the performance of the solar cell. However, the ternary blended organic polymer, due to excessive mixing, can cause serious aggregation between polymer acceptors, which is not conducive to the effective transmission of carrier ions, resulting in poor stability of the solar cell in high and low temperature environments.

[0007] Therefore, providing an active layer that can avoid the blending of polymer donors and polymer acceptors, reduce the aggregation and recombination ability of polymers, and improve the carrier transmission capacity, thereby ensuring the excellent photoelectric conversion efficiency of organic solar cells and effectively improving the cycle stability of the battery under high and low temperature conditions has become an urgent problem to be solved. Summary of the invention

[0008] In order to solve the above technical problems, the purpose of the present invention is to provide a full polymer active layer and its preparation method and application. The present invention provides a full polymer active layer with a quasi-planar heterojunction structure, which can effectively suppress the transition miscibility between the polymer donor and the polymer acceptor and reduce the recombination of carriers during the transmission process; at the same time, a small amount of polymer donor is doped in the polymer acceptor in the second active layer to optimize the morphology of the active layer, reduce the aggregation between the polymer acceptors, and promote the transmission of carriers, thereby obtaining an organic solar cell with excellent photoelectric conversion efficiency and good cycle stability under high and low temperature conditions.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides an all-polymer active layer, which is a quasi-planar heterojunction structure. The all-polymer active layer includes a first active layer and a second active layer arranged on the first active layer, the first active layer includes a first polymer donor, and the second active layer includes a polymer acceptor and a second polymer donor doped in the polymer acceptor.

[0011] The present invention uses a first polymer donor as the first active layer and a polymer acceptor doped with a small amount of a second polymer donor as the second active layer, thereby forming a full-polymer active layer with a quasi-planar heterojunction structure. The active layer can inhibit the transition miscibility between the polymer donor and the polymer acceptor, avoid excessive phase size, reduce excessive aggregation of the polymer, and thus reduce the recombination of carriers during transmission. While ensuring the excellent photoelectric conversion efficiency of the organic solar cell, the cycle stability of the solar cell under high and low temperature conditions is greatly improved.

[0012] The present invention dopes a small amount of polymer donor into the polymer receptor, so that the polymer receptor in the second active layer has a good active layer morphology, significantly reduces the aggregation between the polymer receptors, optimizes the size distribution of the polymer receptors, and is more conducive to the transmission of carriers. At the same time, the receptor in the second active layer of the present invention adopts a polymer receptor, abandons the traditional small molecule receptor, ensures that the polymer receptor has good material stability, and further improves the stability of the organic solar cell under high and low temperature conditions.

[0013] Preferably, in the second active layer, the doping amount of the second polymer donor is 2.5-5%, for example, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0014] In the present invention, if the doping amount of the second polymer donor in the second active layer is too much, the polymer acceptor film will become rough, which is not conducive to the transmission of carriers; if the doping amount is too little, the acceptor film will remain in its original state, and the effect of improving device performance is not obvious.

[0015] Preferably, the thickness of the first active layer is 50-60 nm, for example, 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm or 60 nm.

[0016] Preferably, the thickness of the second active layer is 40-50 nm, for example, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm or 50 nm.

[0017] In the present invention, if the thickness of the first active layer is too thick, the recombination loss in the hole transmission process increases, thereby reducing the hole transmission efficiency; if the thickness of the first active layer is too thin, the light absorption capacity of the active layer in the range of 400-700nm will be significantly weakened, thereby affecting the generation process of excitons and greatly reducing the photovoltaic performance of the device; if the thickness of the second active layer is too thick, the recombination loss in the electron transmission process increases, thereby reducing the electron transmission efficiency; if the thickness of the second active layer is too thin, the light absorption capacity of the active layer in the range of 700-900nm will be significantly weakened, thereby affecting the generation process of excitons and greatly reducing the photovoltaic performance of the device.

[0018] Preferably, the total thickness of the all-polymer active layer is 90-110 nm.

[0019] If the total thickness of the all-polymer active layer of the present invention is too thick, the charge recombination ability will be enhanced, resulting in a decrease in the photoelectric conversion efficiency of the solar cell. If the total thickness of the active layer is too thin, too little charge is generated, which also results in a decrease in the photoelectric conversion efficiency of the solar cell.

[0020] Preferably, the first polymer donor and the second polymer donor independently include any one of PM6, PM7 or PBDB-T-SF.

[0021] Preferably, the polymer acceptor comprises any one of PY-IT, PY-DT or PY-FT.

[0022] The present invention achieves good cross-linking properties of donor and acceptor molecules by screening different polymer donor and polymer acceptor materials, and further enables the solar cell to have relatively excellent stability under high or low temperature conditions.

[0023] In a second aspect, the present invention provides a method for preparing the all-polymer active layer as described in the first aspect, the preparation method comprising the following steps:

[0024] (1) mixing a first polymer donor and a first solvent to obtain a first active layer precursor solution;

[0025] doping a second polymer donor into the polymer receptor to obtain a polymer dopant, and performing a second mixing of the polymer dopant and a second solvent to obtain a second active layer precursor solution;

[0026] (2) Spin coating the first active layer precursor solution obtained in step (1) on a substrate, and then spin coating the second active layer precursor solution, and after annealing, obtain the all-polymer active layer.

[0027] In step (1) of the present invention, the preparation of the first active layer precursor solution and the preparation of the second active layer precursor solution are not precedence-specific.

[0028] The present invention prepares a full polymer active layer of a quasi-planar heterojunction structure by a layer-by-layer spin coating process using a first active layer precursor solution containing a first polymer donor and a second active layer precursor solution containing a polymer dopant. The layer-by-layer spin coating process used achieves good morphology of both the full polymer donor molecules and the polymer acceptor layer doped with a small amount of polymer donors, and can achieve orderly stacking of the polymer donors in the first active layer while avoiding the transition miscibility with the polymer acceptors in the second active layer, thereby reducing the recombination of carriers during transmission; at the same time, the introduction of the doped polymer donor in the second active layer optimizes the morphology of the polymer acceptors in the second active layer, inhibits the aggregation between the polymer acceptor molecules, and improves the charge transmission capacity, thereby improving the photoelectric conversion efficiency of the organic solar cell, and further greatly improving the cycle stability of the solar cell under high and low temperature conditions.

[0029] The present invention has a simple operation process and an obvious optimization effect, plays an important role in promoting further understanding of the relationship between the active layer processing technology and the device stability, and has a bright application prospect in the photovoltaic field.

[0030] Preferably, in step (1), the mass ratio of the amount of the first polymer donor added to the total mass of the polymer acceptor and the doped second polymer donor is (0.9-1.1):(1.1-1.3), wherein the selection range of the first polymer donor is 0.9-1.1, such as 0.9, 1.0 or 1.1, etc.; the selection range of the polymer acceptor doped with the second polymer donor is 1.1-1.3, such as 1.1, 1.2 or 1.3, etc.

[0031] Preferably, in step (1), the first solvent and the second solvent independently include any one of chloroform, chlorobenzene or toluene, or a combination of at least two of them.

[0032] Preferably, in step (1), the mass volume ratio of the polymer donor to the first solvent is 7.0-8.0 mg / mL, for example, 7 mg / mL, 7.1 mg / mL, 7.2 mg / mL, 7.3 mg / mL, 7.4 mg / mL, 7.5 mg / mL, 7.6 mg / mL, 7.7 mg / mL, 7.8 mg / mL, 7.9 mg / mL or 8.0 mg / mL, etc.

[0033] Preferably, the temperature of the first mixing in step (1) is 50-60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, etc.

[0034] Preferably, the first mixing time in step (1) is 120 to 140 min, for example, 120 min, 122 min, 124 min, 126 min, 128 min, 130 min, 132 min, 134 min, 136 min, 138 min or 140 min, etc.

[0035] Preferably, the first mixing method in step (1) includes a first stirring, and the rotation speed of the first stirring is preferably 200-300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm, etc.

[0036] Preferably, in step (1), the mass volume ratio of the polymer dopant to the second solvent is 8.0 to 9.0 mg / mL, for example, 8.0 mg / mL, 8.1 mg / mL, 8.2 mg / mL, 8.3 mg / mL, 8.4 mg / mL, 8.5 mg / mL, 8.6 mg / mL, 8.7 mg / mL, 8.8 mg / mL, 8.9 mg / mL or 9.0 mg / mL, etc.

[0037] Preferably, in step (1), additives are also added during the second mixing process.

[0038] Preferably, the additive includes any one of chloronaphthalene, bromonaphthalene or fluoronaphthalene, or a combination of at least two thereof.

[0039] Preferably, the additive is added in an amount of 1-2% of the total volume of the second active layer precursor solution, for example, 1.0%, 1.2%, 1.4%, 1.6%, 1.8% or 2.0%.

[0040] In the present invention, the additive is introduced in the preparation process of the second active layer precursor solution in order to delay the drying time of the polymer receptor molecules and thus optimize the morphology of the polymer receptor layer.

[0041] Preferably, the temperature of the second mixing in step (2) is 50-60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, etc.

[0042] Preferably, the second mixing time in step (1) is 120 to 140 min, for example, 120 min, 122 min, 124 min, 126 min, 128 min, 130 min, 132 min, 134 min, 136 min, 138 min or 140 min, etc.

[0043] Preferably, the second mixing method in step (1) includes a second stirring, and the rotation speed of the second stirring is preferably 200-300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm, etc.

[0044] Preferably, during the spin coating of the first active layer precursor solution, the spin coating speed is 2000-3000 rpm, for example, 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, 2400 rpm, 2500 rpm, 2600 rpm, 2700 rpm, 2800 rpm, 2900 rpm or 3000 rpm.

[0045] Preferably, during the spin coating of the first active layer precursor solution, the spin coating time is 20 to 30 s, for example, 20 s, 21 s, 22 s, 23 s, 24 s, 25 s, 26 s, 27 s, 28 s, 29 s or 30 s.

[0046] Preferably, during the spin coating of the second active layer precursor solution, the spin coating speed is 3000-5000 rpm, for example, 3000 rpm, 3200 rpm, 3400 rpm, 3600 rpm, 3800 rpm, 4000 rpm, 4200 rpm, 4400 rpm, 4600 rpm, 4800 rpm or 5000 rpm.

[0047] Preferably, during the spin coating of the second active layer precursor solution, the spin coating time is 20 to 30 s, for example, 20 s, 21 s, 22 s, 23 s, 24 s, 25 s, 26 s, 27 s, 28 s, 29 s or 30 s.

[0048] The present invention helps to achieve good interface contact between the first active layer and the second active layer by adjusting the rotation speed of spin coating of the first active layer precursor solution and the second active layer precursor solution, reduces the recombination ability of carriers at the contact interface between the polymer donor and the polymer acceptor, and promotes the charge transfer performance, which is of great significance for further suppressing the transition miscibility phenomenon between the donor and acceptor molecules and improving the cycle stability of solar cells under high and low temperature conditions.

[0049] In addition, the spin coating speed during the spin coating process will affect the thickness of the first active layer and the second active layer in the prepared all-polymer active layer. Specifically, if the speed is too high, the active layer film will become thinner, thereby reducing the light absorption capacity of the active layer. If the speed is too low, the active layer will be too thick, affecting the transfer and recombination of charges. Therefore, too high or too low a speed will lead to a decrease in device performance.

[0050] Preferably, the annealing temperature in step (2) is 80-100°C, for example, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C.

[0051] Preferably, the annealing time in step (2) is 5 to 15 min, for example, 5 min, 7 min, 9 min, 11 min, 13 min or 15 min.

[0052] In a third aspect, the present invention provides an organic solar cell, comprising a substrate, a first carrier transport layer, an active layer, a second carrier transport layer and a metal counter electrode stacked in sequence, wherein the active layer comprises the all-polymer active layer as described in the first aspect.

[0053] The organic solar cell provided by the present invention adopts a specific all-polymer active layer, which greatly improves the photoelectric conversion efficiency of the organic solar cell and the cycle stability under high and low temperature conditions.

[0054] Preferably, the substrate comprises ITO conductive glass.

[0055] Preferably, the first carrier transport layer comprises PEDOT:PSS.

[0056] Preferably, the metal counter electrode comprises any one of silver, aluminum or gold, or a combination of at least two of them.

[0057] In a fourth aspect, the present invention provides a method for preparing an organic solar cell as described in the third aspect, the method comprising:

[0058] A first carrier transport layer, the all-polymer active layer as described in the first aspect, a second carrier transport layer and a metal counter electrode are sequentially arranged on the surface of the substrate, and annealed to obtain the organic solar cell.

[0059] Preferably, in the process of preparing an organic solar cell, the annealing temperature is 80-100°C, for example, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C.

[0060] Preferably, in the process of preparing the organic solar cell, the annealing time is 5 to 15 min, for example, 5 min, 7 min, 9 min, 11 min, 13 min or 15 min.

[0061] Preferably, the method for preparing the first carrier transport layer comprises:

[0062] A precursor solution containing PEDOT and PSS is spin-coated on a substrate and annealed to obtain the first carrier transport layer.

[0063] Preferably, in the process of preparing the first carrier transport layer, the spin coating speed is 3000-5000rpm, for example, 3000rpm, 3200rpm, 3400rpm, 3600rpm, 3800rpm, 4000rpm, 4200rpm, 4400rpm, 4600rpm, 4800rpm or 5000rpm.

[0064] Preferably, in the process of preparing the first carrier transport layer, the spin coating time is 20 to 30 s, for example, 20 s, 21 s, 22 s, 23 s, 24 s, 25 s, 26 s, 27 s, 28 s, 29 s or 30 s.

[0065] Preferably, in the process of preparing the first carrier transport layer, the annealing temperature is 160-170°C, for example, 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C or 170°C, etc.

[0066] Preferably, in the process of preparing the first carrier transport layer, the annealing time is 5 to 15 min, for example, 5 min, 7 min, 9 min, 11 min, 13 min or 15 min.

[0067] As a preferred technical solution of the method for preparing an organic solar cell according to the present invention, the preparation method comprises:

[0068] (a) spin coating a precursor solution containing PEDOT:PSS on a substrate at a spin coating speed of 3000 to 5000 rpm for 20 to 30 seconds, and annealing at a temperature of 160 to 170° C. for 5 to 15 minutes to obtain the first carrier transport layer;

[0069] (b) spin coating a first active layer precursor solution on the first carrier transport layer at a spin coating speed of 2000-3000 rpm for 20-30 s, then spin coating a second active layer precursor solution at a spin coating speed of 3000-5000 rpm for 20-30 s, and annealing at a temperature of 80-100° C. for 5-15 min to obtain a full polymer active layer;

[0070] (c) sequentially disposing a second carrier transport layer and a metal counter electrode on the surface of the all-polymer active layer, and annealing at a temperature of 80 to 100° C. for 5 to 15 minutes to obtain the organic solar cell.

[0071] Compared with the prior art, the present invention has at least the following beneficial effects:

[0072] (1) The all-polymer active layer with a quasi-planar heterojunction structure provided by the present invention can reduce the transition miscibility between the polymer donor and the polymer acceptor, reduce the recombination of carriers during the transmission process, and effectively promote the charge transmission performance; at the same time, a small amount of polymer donor is doped in the polymer acceptor in the second active layer, so that the second active layer has a good morphology, significantly reduces the aggregation between polymer acceptors, optimizes the size distribution of polymer acceptors, and is more conducive to the transmission of carriers, thereby obtaining an organic solar cell with excellent photoelectric conversion efficiency and good cycle stability under high and low temperature conditions. In addition, the use of polymer acceptors in the second active layer of the present invention abandons traditional small molecule acceptors, further ensures the good material stability of the polymer acceptors, and further improves the stability of the organic solar cell under high and low temperature conditions.

[0073] (2) The present invention spin-coats the first active layer precursor solution and the second active layer precursor solution respectively by a layer-by-layer spin-coating process, thereby obtaining a full polymer active layer with a quasi-planar heterojunction structure. The layer-by-layer spin-coating process used achieves good morphology for both the full polymer donor molecules and the polymer acceptor layer doped with a small amount of polymer donors, and can achieve orderly stacking of the polymer donors in the first active layer while avoiding the transitional miscibility with the polymer acceptors in the second active layer, thereby reducing the recombination of carriers during transmission; at the same time, the introduction of doped polymer donors in the second active layer optimizes the morphology of the second active layer, reduces the aggregation between polymer acceptor molecules, and improves the charge transmission capacity, thereby improving the photoelectric conversion efficiency of organic solar cells and greatly improving the cycle stability of solar cells under high and low temperature conditions.

[0074] (3) The organic solar cell provided by the present invention adopts a specific all-polymer active layer, which greatly improves the photoelectric conversion efficiency of the organic solar cell and the cycle stability under high and low temperature conditions. Among them, the photoelectric conversion efficiency of the quasi-heterojunction device organic solar cell of the present invention can reach up to 17.41%, the photoelectric conversion efficiency retention rate at 205K can reach up to 91.13%, and the photoelectric conversion efficiency retention rate at 355K can reach up to 91.38%. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a test chart of the cyclic stability of organic solar cells assembled with the all-polymer active layers in Examples 1, 2 and 3 at 205K.

[0076] Figure 2This is a test chart of the cyclic stability of organic solar cells assembled with the all-polymer active layers in Examples 1, 2 and 3 at 355K.

[0077] Figure 3 This is a test chart of the cyclic stability of organic solar cells assembled with all-polymer active layers in Comparative Examples 1, 2 and 3 at 205K.

[0078] Figure 4 This is a test chart of the cyclic stability of organic solar cells assembled with all-polymer active layers in Comparative Examples 1, 2 and 3 at 335K.

[0079] Figure 5 This is a morphology diagram of the all-polymer active layer in Example 1.

[0080] Figure 6 This is a morphology diagram of the all-polymer active layer in Example 2.

[0081] Figure 7 This is a morphology diagram of the all-polymer active layer in Example 3.

[0082] Figure 8 This is the morphology of the all-polymer active layer in Comparative Example 1.

[0083] Fig. 9 This is the morphology of the all-polymer active layer in Comparative Example 2.

[0084] Fig.10 This is the morphology of the all-polymer active layer in Comparative Example 3. DETAILED DESCRIPTION

[0085] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0086] In step (1) in the following embodiments, the preparation of the first active layer precursor solution and the preparation of the second active layer precursor solution are carried out in no particular order.

[0087] The preparation method of the substrate used in the following examples is:

[0088] Using ITO conductive glass (thickness of 200 nm) as the substrate, the PEDOT:PSS precursor solution was spin-coated on the substrate at a spin coating speed of 4000 rpm and a spin coating time of 30 s. After spin coating, it was annealed at 165° C. for 10 min to obtain a substrate with a stacked substrate and a first carrier transport layer.

[0089] Example 1

[0090] This embodiment provides an all-polymer active layer with a quasi-planar heterojunction structure, the total thickness of the all-polymer active layer is 100nm, the all-polymer active layer includes a first active layer and a second active layer stacked in sequence from bottom to top, the first active layer includes a polymer donor PM6, the thickness of the first active layer is 55nm, the second active layer includes a polymer acceptor PY-IT and a polymer donor PM6 with a doping amount of 4%, and the thickness of the second active layer is 45nm.

[0091] This embodiment provides a method for preparing the above-mentioned all-polymer active layer:

[0092] (1) 1 mg of polymer donor PM6 was mixed with 137 μL of chloroform, and stirred at 50° C. for 120 min at a stirring speed of 200 rpm to obtain a first active layer precursor solution;

[0093] 0.05 mg of PM6 and 1.2 mg of PY-IT were mixed, and then 143 μL of chloroform was added. The mixture was stirred at 50°C for 90 min and the stirring speed was 200 rpm. 2.15 μL of chloronaphthalene additive was added, and the stirring was continued at the same temperature and speed for 30 min to obtain the second active layer precursor solution.

[0094] (2) Spin coating the first active layer precursor solution on the first carrier transport layer in the substrate at a speed of 2500 rpm for 25 s, and then spin coating the second active layer precursor solution at a speed of 4000 rpm for 25 s. Then, annealing was performed at 90° C. for 10 min to obtain a full polymer active layer.

[0095] This embodiment also provides an organic solar cell, which includes an ITO conductive glass substrate, a PEDOT:PSS first carrier transport layer, the above-mentioned all-polymer active layer, a PNDIT-F3N second carrier transport layer and a silver metal counter electrode stacked in sequence.

[0096] Example 2

[0097] This embodiment provides an all-polymer active layer with a quasi-planar heterojunction structure, the total thickness of the all-polymer active layer is 106nm, the all-polymer active layer includes a first active layer and a second active layer stacked in sequence from bottom to top, the first active layer includes a polymer donor PM6, the thickness of the first active layer is 58nm, the second active layer includes a polymer acceptor PY-DT and a polymer donor PM6 with a doping amount of 3%, and the thickness of the second active layer is 48nm.

[0098] This embodiment provides a method for preparing the above-mentioned all-polymer active layer:

[0099] (1) 1 mg of polymer donor PM6 was mixed with 137 μL of chloroform, and stirred at 55° C. for 130 min at a stirring speed of 250 rpm to obtain a first active layer precursor solution;

[0100] 0.036 mg of PM6 and 1.164 mg of PY-DT were mixed, and then 143 μL of chloroform was added. The mixture was stirred at 55°C for 100 min at a stirring speed of 250 rpm. 2.15 μL of chloronaphthalene additive was added, and stirring was continued at the same temperature and speed for 30 min to obtain the second active layer precursor solution.

[0101] (2) Spin coating the first active layer precursor solution on the first carrier transport layer in the substrate at a speed of 2300 rpm for 25 s, and then spin coating the second active layer precursor solution at a speed of 3500 rpm for 25 s. Then, annealing was performed at 100° C. for 5 min to obtain a full polymer active layer.

[0102] This embodiment also provides an organic solar cell, which includes an ITO conductive glass substrate, a PEDOT:PSS first carrier transport layer, the above-mentioned all-polymer active layer, a PDINO second carrier transport layer and an aluminum metal counter electrode stacked in sequence.

[0103] Example 3

[0104] The present embodiment provides an all-polymer active layer with a quasi-planar heterojunction structure. The total thickness of the all-polymer active layer is 96 nm. The first active layer and the second active layer are stacked in sequence from bottom to top. The first active layer includes a polymer donor PM6, and the thickness of the first active layer is 53 nm. The second active layer includes a polymer acceptor PY-FT and a polymer donor PM6 with a doping amount of 5%, and the thickness of the second active layer is 43 nm.

[0105] This embodiment provides a method for preparing the above-mentioned all-polymer active layer:

[0106] (1) 1 mg of polymer donor PM6 was mixed with 137 μL of chloroform, and stirred at 58° C. for 125 min at a stirring speed of 280 rpm to obtain a first active layer precursor solution;

[0107] 0.06 mg of PM6 and 1.14 mg of PY-FT were mixed, and then 143 μL of chloroform was added. The mixture was stirred at 58°C for 95 min and the stirring speed was 280 rpm. 2.15 μL of chloronaphthalene additive was added, and the stirring was continued at the same temperature and speed for 30 min to obtain the second active layer precursor solution.

[0108] (2) Spin coating the first active layer precursor solution on the first carrier transport layer in the substrate at a spin coating speed of 2800 pm for 25 s, and continue to spin coat the second active layer precursor solution at a spin coating speed of 4500 rpm for 25 s. Then, anneal at 85°C for 15 min to obtain a full polymer active layer.

[0109] This embodiment also provides an organic solar cell, which includes an ITO conductive glass substrate, a PEDOT:PSS first carrier transport layer, the above-mentioned all-polymer active layer, a PDINN second carrier transport layer and a gold metal counter electrode stacked in sequence.

[0110] The cycle stability test diagram of the organic solar cell assembled with the all-polymer active layer provided in the above-mentioned Examples 1, 2 and 3 at 205K is shown in FIG. Figure 1 As shown in the figure, it can be seen that the all-polymer active layer provided by Examples 1-3 is applied to an organic solar cell at low temperature, and good low-temperature cycle stability can be obtained; the cycle stability test diagram at 355K is shown in Figure 2 As shown in the figure, it can be seen that the all-polymer active layer provided in Examples 1-3 is applied to organic solar cells and can obtain good high-temperature cycle stability.

[0111] Example 4

[0112] In this embodiment, except that the doping amount of PM6 in the second active layer is 2%, other conditions are the same as those in Embodiment 1.

[0113] Example 5

[0114] In this embodiment, except that the doping amount of PM6 in the second active layer is 6%, other conditions are the same as those in Embodiment 1.

[0115] Example 6

[0116] In the present embodiment, in addition to providing a full polymer active layer, the thickness of the second active layer is kept unchanged, and the thickness of the first active layer is changed to 47nm, corresponding to the total thickness of the full polymer active layer is 92nm; accordingly, in the preparation method of the full polymer active layer, the rotation speed of the spin coating of the first active layer precursor solution is 3400rpm, and other conditions are the same as those in Example 1.

[0117] Example 7

[0118] In the present embodiment, in addition to providing a full polymer active layer, the thickness of the second active layer is kept unchanged, and the thickness of the first active layer is changed to 62nm, corresponding to the total thickness of the full polymer active layer of 107nm; accordingly, in the preparation method of the full polymer active layer, the rotation speed of the spin coating of the first active layer precursor solution is 1700rpm, and other conditions are the same as those in Example 1.

[0119] Example 8

[0120] In the present embodiment, in addition to providing the all-polymer active layer, the thickness of the first active layer is kept unchanged, and the thickness of the second active layer is changed to 37nm, corresponding to the total thickness of the all-polymer active layer is 92nm; accordingly, in the preparation method of the all-polymer active layer, the rotation speed of the spin coating of the second active layer precursor solution is 5400rpm, and other conditions are the same as those in Example 1.

[0121] Example 9

[0122] In the present embodiment, in addition to providing the all-polymer active layer, the thickness of the first active layer is kept unchanged, and the thickness of the second active layer is changed to 54nm, corresponding to the total thickness of the all-polymer active layer is 109nm; accordingly, in the preparation method of the all-polymer active layer, the rotation speed of the spin coating of the second active layer precursor solution is 2500rpm, and other conditions are the same as those in Example 1.

[0123] Example 10

[0124] In the present embodiment, in addition to providing the all-polymer active layer, the thickness of the first active layer is kept unchanged, and the thickness of the second active layer is changed to 31 nm, corresponding to the total thickness of the all-polymer active layer is 86 nm; accordingly, in the preparation method of the all-polymer active layer, the rotation speed of the spin coating of the second active layer precursor solution is 5800 rpm, and other conditions are the same as those in Example 1.

[0125] Embodiment 11

[0126] In the present embodiment, in addition to providing the all-polymer active layer, the thickness of the first active layer is kept unchanged, and the thickness of the second active layer is changed to 59 nm, corresponding to the total thickness of the all-polymer active layer is 119 nm; accordingly, in the preparation method of the all-polymer active layer, the rotation speed of the spin coating of the second active layer precursor solution is 2300 rpm, and other conditions are the same as those in Example 1.

[0127] Comparative Example 1

[0128] This comparative example provides a full polymer blended active layer, the active layer includes a blended polymer donor PM6 and a polymer acceptor PY-IT, and the thickness of the active layer is 100 nm. Its contents are the same as those of Example 1.

[0129] Accordingly, this comparative example provides a method for preparing a fully polymer blended active layer, comprising the following steps:

[0130] (1) Weigh 1.05 mg of polymer donor PM6 and 1.2 mg of polymer acceptor PY-IT, add 137 chloroform, stir at 50 °C for 90 min, and stir at 200 rpm. Add 2.75 μL of chloronaphthalene additive, and continue stirring at the same temperature and speed for 30 min to obtain a polymer blend precursor solution.

[0131] (2) Spin coating the polymer blended precursor solution on the first carrier transport layer in the substrate at a spin coating speed of 3000 rpm for 50 s, and then annealing at 90° C. for 10 min to obtain a full polymer blended active layer.

[0132] Comparative Example 2

[0133] This comparative example provides a full polymer blended active layer, the active layer includes a blended polymer donor PM6 and a polymer acceptor PY-DT, and the thickness of the active layer is 106 nm. Its contents are the same as those of Example 2.

[0134] Accordingly, this comparative example provides a method for preparing a fully polymer blended active layer:

[0135] (1) Weigh 1.036 mg of polymer donor PM6 and 1.164 mg of polymer acceptor PY-DT, add 137 μL of chloroform, stir at 55 °C for 100 min, and stir at 250 rpm. Add 2.75 μL of chloronaphthalene additive, and continue stirring at the same temperature and speed for 30 min to obtain a polymer blend precursor solution.

[0136] (2) Spin coating the polymer blended precursor solution onto the first carrier transport layer in the substrate at a spin coating speed of 2800 rpm for 50 s, and then annealing at 100° C. for 5 min to obtain a full polymer blended active layer.

[0137] Comparative Example 3

[0138] This comparative example provides a full polymer blended active layer, the active layer includes a blended polymer donor PM6 and a polymer acceptor PY-FT, and the thickness of the active layer is 96 nm. Its contents are the same as those of Example 3.

[0139] Accordingly, this comparative example provides a method for preparing a fully polymer blended active layer:

[0140] (1) Weigh 1.06 mg of polymer donor PM6 and 1.14 mg of polymer acceptor PY-FT, add 137 μL of chloroform, stir at 58 °C for 95 min, and stir at 280 rpm. Add 2.75 μL of chloronaphthalene additive, and continue stirring at the same temperature and speed for 30 min to obtain a polymer blend precursor solution.

[0141] (2) Spin coating the polymer blended precursor solution on the first carrier transport layer in the substrate at a spin coating speed of 3200 rpm for 50 s, and then annealing at 85° C. for 15 min to obtain a full polymer blended active layer.

[0142] The cycle stability test graph of the organic solar cell assembled with the all-polymer active layer provided in Comparative Examples 1, 2 and 3 at 205K is shown in the figure below: Figure 3 As shown in the figure, it can be seen that at a low temperature of 205K, the organic solar cell uses an active layer obtained by blending a polymer donor and a polymer acceptor, which makes the cycle stability of the organic solar cell at low temperature poor; the cycle stability test diagram at 355K is shown in Figure 4 As shown in the figure, it can be seen that the organic solar cell uses an active layer obtained by blending a polymer donor and a polymer acceptor, which makes the organic solar cell have poor cycle stability at low temperatures.

[0143] Comparative Example 4

[0144] In this comparative example, except that the polymer donor PM6 and the polymer acceptor PY-IT doped in the second active layer are replaced by the small molecule acceptor Y6, other conditions are the same as those in Example 1.

[0145] Comparative Example 5

[0146] In this comparative example, except that the polymer donor molecules doped in the second active layer are omitted, other conditions are the same as those in Example 1.

[0147] Comparative Example 6

[0148] In this comparative example, the first active layer is omitted, and only the second active layer - doped polymer donor PM6 and polymer donor PY-IT are retained. Correspondingly, in the preparation method of the all-polymer active layer, the second active layer precursor solution is directly spin-coated on the first carrier transport layer, and other conditions are the same as in Example 1.

[0149] The organic solar cells in the above Examples 1-11 and Comparative Examples 1-6 were subjected to performance tests:

[0150] The device was characterized using an IV tester under standard test conditions, i.e., in a nitrogen atmosphere under a simulated AM 1.5G (AAA grade, XES-70S1) light source. The light intensity in front of the cell sample was calibrated to 100 mW / cm using a reference silicon cell. 2 The device current density-voltage (JV) was measured using a computer-controlled Keithley 2400 Source Measure Unit, and recorded from -0.1V to 1.2V along the forward scanning direction to measure the organic solar photoelectric conversion efficiency at different temperatures, and the photoelectric conversion efficiency retention rate after 5 cycles at 205K and the photoelectric conversion efficiency retention rate after 5 cycles at 355K were calculated, where the photoelectric conversion efficiency retention rate = PCE (%) after cycling at 205K or 355K / initial test PCE (%). The test results are shown in Table 1:

[0151] Table 1

[0152]

[0153] (1) It can be seen from Examples 1 to 3 that the present invention uses a first polymer donor as the first active layer and a polymer acceptor doped with a small amount of a second polymer donor as the second active layer to form a full polymer active layer with a quasi-planar heterojunction structure, which can reduce the transition miscibility between the polymer donor and the polymer acceptor, avoid excessive phase size, reduce excessive aggregation, thereby reducing the recombination of carriers during transmission, and greatly improve the cycle stability of the solar cell under high or low temperature conditions.

[0154] Figure 5 is a morphology diagram of the all-polymer active layer in Example 1, Figure 6 is a morphology diagram of the all-polymer active layer in Example 2, Figure 7 is a morphology diagram of the all-polymer active layer in Example 3. Figure 5-7 It can be seen that compared with the PM6 / PY-DT blend film, the PM6 / PY-IT blend film has a smaller root mean square roughness (Rq=1.23nm vs. Rq=1.58nm).

[0155] (2) By comparing Example 1 with Examples 4-5, it can be seen that in the present invention, if the doping amount of the second polymer donor in the second active layer is too much, the device performance will be reduced, mainly because there are too many interfaces at the acceptor interface, which affects the efficient transmission of carriers; too little doping will also lead to a decrease in device performance, mainly because the doping amount is too little to optimize the device morphology.

[0156] (3) By comparing Example 1 with Examples 6-7, it can be seen that in the present invention, if the thickness of the first active layer is too thick, it will exceed the hole transmission capacity range, thereby affecting the device efficiency; if the thickness of the first active layer is too thin, it will cause the device's ability to capture photons in the range of 400-700nm to decrease, thereby reducing the device efficiency.

[0157] (4) By comparing Example 1 with Examples 8-9, it can be seen that if the thickness of the second active layer in the present invention is too thick, it will exceed the electron transmission capacity range, thereby reducing the device efficiency; if the thickness of the second active layer is too thin, it will cause the device's ability to capture photons in the range of 700-900nm to decrease, thereby reducing the device efficiency.

[0158] (5) By comparing Example 1 with Examples 10-11, it can be seen that in the present invention, if the total thickness of the all-polymer active layer is too thick, the charge recombination ability will be enhanced, resulting in a decrease in the photoelectric conversion efficiency of the solar cell. If the total thickness of the active layer is too thin, too little charge is generated, which also results in a decrease in the photoelectric conversion efficiency of the solar cell.

[0159] (6) By comparing Example 1 with Comparative Examples 1-3, it can be seen that the present invention does not adopt a layer-by-layer coating process to form the first active layer and the second active layer of the quasi-planar heterojunction structure as the active layer, but rather blends the polymer donor and the polymer acceptor. When the active layer is prepared by a one-step spin coating process, it will lead to serious transition miscibility between polymer molecules, transition aggregation, and excessively large phase size in the active layer, which leads to recombination of carriers during transmission and poor stability of the organic solar cell, thereby resulting in a significant decrease in the photoelectric conversion efficiency of the organic solar cell and extremely poor cycle stability under high and low temperature conditions.

[0160] Figure 8 This is the morphology of the all-polymer active layer in Comparative Example 1. Fig. 9 This is the morphology of the all-polymer active layer in Comparative Example 2. Fig.10 This is the morphology of the all-polymer active layer in Comparative Example 3. Figure 8-10 It can be seen that due to the influence of the donor polymer, the RMS roughness of the active layer increases significantly, which is not conducive to the transport of carriers, leads to increased charge recombination, and thus reduces the device efficiency.

[0161] (7) By comparing Example 1 with Comparative Example 4, it can be seen that if the second active layer doped with the polymer donor and the polymer acceptor is replaced with the small molecule Y6 in the present invention, the stability of the second active layer material will be poor, thereby resulting in poor photoelectric conversion efficiency of the organic solar cell and poor cycle stability under high and low temperature conditions.

[0162] (8) By comparing Example 1 with Comparative Example 5, it can be seen that if the polymer donor is not doped in the polymer acceptor of the second active layer in the present invention, it will lead to excessive aggregation of the polymer acceptor molecules in the second active layer, uneven phase size distribution of the acceptor molecules, poor carrier transport capacity, and poor stability of the organic solar cell, thereby resulting in too low photoelectric conversion efficiency of the battery and poor cycle stability.

[0163] (9) By comparing Example 1 with Comparative Example 6, it can be seen that if the first active layer is missing in the present invention, the efficiency of the device will be greatly reduced, mainly because the second active layer, as an electron acceptor material, cannot transport holes well.

[0164] In summary, the present invention provides a full-polymer active layer with a quasi-planar heterojunction structure, which can effectively suppress the transition miscibility phenomenon between the polymer donor and the polymer acceptor and reduce the recombination of carriers during the transmission process; at the same time, a small amount of polymer donor is doped into the polymer acceptor in the second active layer to optimize the morphology of the active layer, reduce the aggregation between the polymer acceptors, and promote the transmission of carriers, thereby obtaining an organic solar cell with excellent photoelectric conversion efficiency and good cycle stability under high and low temperature conditions.

[0165] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A fully polymer active layer, characterized in that: The all-polymer active layer is a quasi-planar heterojunction structure, comprising a first active layer and a second active layer disposed on the first active layer, wherein the first active layer comprises a first polymer donor, and the second active layer comprises a polymer acceptor and a second polymer donor doped in the polymer acceptor.

2. The all-polymer active layer according to claim 1, characterized in that: In the second active layer, the doping amount of the second polymer donor is 2.5-5%.

3. The all-polymer active layer according to claim 1, characterized in that: The thickness of the first active layer is 50-60 nm; The thickness of the second active layer is 40 to 50 nm; The total thickness of the all-polymer active layer is 90-110 nm.

4. The all-polymer active layer according to claim 1, characterized in that: The first polymer donor and the second polymer donor independently include any one of PM6, PM7 or PBDB-T-SF; The polymer acceptor includes any one of PY-IT, PY-DT or PY-FT.

5. A method for preparing a full polymer active layer according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a first polymer donor and a first solvent to obtain a first active layer precursor solution; doping a second polymer donor into the polymer receptor to obtain a polymer dopant, and performing a second mixing of the polymer dopant and a second solvent to obtain a second active layer precursor solution; (2) Spin coating the first active layer precursor solution obtained in step (1) on a substrate, and then spin coating the second active layer precursor solution, and after annealing, obtain the all-polymer active layer.

6. The method for preparing the all-polymer active layer according to claim 5, characterized in that: In step (1), the mass ratio of the amount of the first polymer donor added to the total mass of the polymer acceptor and the doped second polymer donor is (0.9-1.1):(1.1-1.3); Step (1) the first solvent and the second solvent independently include any one of chloroform, chlorobenzene or toluene or a combination of at least two thereof; Step (1) The temperature of the first mixing is 50-60° C.; Step (1) The first mixing time is 120 to 140 minutes; Step (1) the temperature of the second mixing is 50-60° C.; The second mixing time in step (1) is 120 to 140 minutes.

7. The method for preparing the all-polymer active layer according to claim 5, characterized in that: In step (2), during the spin coating of the first active layer precursor solution, the spin coating speed is 2000-3000 rpm; During the spin coating of the first active layer precursor solution, the spin coating time is 20 to 30 seconds; During the spin coating of the second active layer precursor solution, the spin coating speed is 3000-5000 rpm; During the spin coating of the second active layer precursor solution, the spin coating time is 20 to 30 seconds.

8. The method for preparing the all-polymer active layer according to claim 5, characterized in that: The annealing temperature in step (2) is 80-100° C. The annealing time in step (2) is 5 to 15 minutes.

9. An organic solar cell, characterized in that: The organic solar cell comprises a substrate, a first carrier transport layer, an active layer, a second carrier transport layer and a metal counter electrode stacked in sequence, and the active layer comprises the all-polymer active layer according to any one of claims 1 to 4.

10. A method for preparing an organic solar cell according to claim 9, characterized in that: The preparation method comprises: A first carrier transport layer, a full polymer active layer as claimed in any one of claims 1 to 4, a second carrier transport layer and a metal counter electrode are sequentially arranged on the surface of the substrate, and annealed to obtain the organic solar cell; In the process of preparing the organic solar cell, the annealing temperature is 80-100° C., and the annealing time is 5-15 minutes.

Citation Information

Patent Citations

  • Ternary blending organic polymer solar cell device

    CN107359243A

  • Organic solar cell based on polymer donor-star-shaped non-fullerene receptor and preparation method thereof

    CN116133443A

  • Organic solar cell based on step-by-step spin-coating mixed heterojunction and preparation method thereof

    CN116782673A

  • Organic solar cell based on photovoltaic active layer in-situ cross-linking curing and preparation method thereof

    CN117794262A

  • Active layer of ternary quasi-plane heterojunction organic solar cell and application thereof

    CN117858524A